Symmetry in Complex Systems - Lopes, António M. (2022)
Complex systems with symmetry arise in many fields, at various length scales, including financial markets, social, transportation, telecommunication and power grid networks, world and country economies, ecosystems, molecular dynamics, immunology, living organisms, computational systems, and celestial and continuum mechanics. The emergence of new order and structure in complex systems means symmetry breaking and transition from unstable to stable states. Modeling complexity attracted many researchers from different areas, dealing both with theoretical concepts and practical applications. This Special Issue seeks to fill the gap between the theory of symmetry-based dynamics and its application to model and analyze complex systems. This Special Issue focuses on the synergies between the theory of symmetry-based dynamics and its application to model and analyze complex systems. It includes 7 manuscripts addressing novel issues and specific topics that illustrate symmetry in complex systems. In the follow-up the selected manuscripts are presented in alphabetic order.